Impact of Preoperative Nutritional Indicator on Poor Postoperative Outcomes in Geriatric Patients with Colorectal Cancer. (21st April 2022) - Nagata, Tomoyuki; Adachi, Yuki; Taniguchi, Akihiro; Kimura, Yu; Iitaka, Daisuke; Iwata, George; Yamaoka, Nobuki
Abstract: The present study aimed to analyze the association between preoperative nutritional assessment and poor postoperative outcomes in geriatric patients with colorectal cancer. This retrospective study included 138 patients aged ≥80 years with colorectal cancer who underwent surgery from January 2013 to December 2018. Patients were classified into two groups according to outcomes, poor group and normal group. Clinicopathological factors were compared between the groups, and the relationships of several nutritional indices were examined. There was no significant difference in sex, age, or preoperative comorbidities. There were significant differences in volume of blood loss and proportion of laparoscopic surgery. The group with poor outcomes had significantly higher neutrophil/lymphocyte ratio (NLR) and modified Glasgow prognostic score (mGPS) than the group with normal outcomes. Multivariate analysis revealed that open approach, high NLR, and category D mGPS were independent risk factors of poor postoperative outcomes in elderly patients with colorectal cancer. Our findings indicate that mGPS and NLR could be useful nutritional indicators of short-term outcomes of surgical treatment in geriatric patients with colorectal cancer. They can be evaluated based on albumin and C-reactive protein levels and blood count, which are inexpensive and beneficial to use in routine clinical practice.